520 A possible easy way to predict response to cardiac resynchronization therapy: the role of QRS index. (8th December 2021) - Coppola, Giuseppe; Novo, Giuseppina; Prezioso, Amedeo; Bonnì, Enrico; Madaudo, Cristina; Campo, Francesco; Sucato, Vincenzo; Ciaramitaro, Gianfranco; Galassi, Alfredo Ruggero; Corrado, Egle
Abstract: Several studies have evaluated the role of QRS duration or QRS narrowing as predictor of response to cardiac resynchronization therapy (CRT) in order to reduce non-responders. However, their results have been conflicting. The aim of our study was to determine the association between the relative change in QRS narrowing index (QI) and clinical outcome and prognosis in patients who underwent CRT implantation. We included 115 patients in whom a CRT device was implanted in accordance with current guidelines. Baseline clinical variables, echocardiographic parameters, and pharmacological therapies were included. QRS duration before and after CRT implantation and QI [(pre implant QRS duration—QRS duration during CRT)/pre implant QRS duration × 100] were measured. After 6 months, a significant improvement in all echocardiographic parameters was observed. In 103 (90%) patients, LVESV decreased by 10% or more. QI was significantly related to reverse remodelling ( r = +0.19; 95% CI: 0.006–0.35, P = 0.049). The cut-off value of QI that predicted best LV reverse remodelling after 6 months of CRT was 12.25% (sensitivity = 65.5%, specificity = 75%, area under the curve = 0.737, P = 0.001). An improvement in their HF clinical composite score at 12 months was found in 23 patients (21%). Considering the improvement in NYHA class, of the 73 patients with QI > 12.25%, 34 (46.5%) had a reduced NYHA class at 12 months post implantation. A statistically significant difference was found between patients with a QI < 12.25%, and those with a QI > 12.25%, in terms of NYHA class worsening ( P 0.04). Also a statistically significant difference was found between the mean of the QI of patients who died from cardiovascular causes and patients who died of other causes. We have also investigated the possible sex differences related to QI; women with QI > 12.25% had a statistically significant greater improvement in LVEF at follow-up than men with QI > 12.25% ( P 0.03). Patients with a larger decrease in QRSd after CRT initiation showed greater echocardiographic reverse remodelling and better outcome from death or cardiovascular hospitalization. Even if larger studies are needed, QI seems to be an easy-to-measure variable that could be used or evaluated to predict CRT response.